International law and peace settlements - Weller, Marc 1960-; Retter, Mark ca. 20./21. Jh; Varga, Andrea 1985- (Cambridge University Press, 2021)
International Law and Peace Settlements provides a systematic and comprehensive assessment of the relationship between international law and peace settlement practice across core settlement issues, e.g. transitional justice, human rights, refugees, self-determination, power-sharing, and wealth-sharing. The contributions address key cross-cutting questions on the legal status of peace agreements, the potential for developing international law, and the role of key actors - such as non-state armed groups, third-state witnesses and guarantors, and the UN Security Council - in the legalisation and internationalisation of settlement commitments. In recent years, significant scholarly work has examined facets of the relationship between international law and peace settlements, through concepts such as jus post bellum and lex pacificatoria. International Law and Peace Settlements drives forward the debate on the legalisation and internationalisation of peace agreements with diverse contributions from leading academics and practitioners in international law and conflict resolution.
Literaturangaben, Register
Keywords: International law; Peace; Aufsatzsammlung